Bibliometric Analysis of Employee Mental Health - Asyifa, Zahra; Martiza, Shanata Putri (West Science Interdisciplinary Studies, 2025)
In the modern world of work, employee mental health is very important, especially amidst increasing work pressure, high professional demands, and rapidly changing work environments. Bibliometric methods were used in this study to analyze research trends in employee mental health. VOSviewer was used to analyze the relationship between authors, institutions, and keywords after data were collected from Publish or Perish software accessed from Google Scholar from 2014 to 2024. The results of the analysis showed that subjects such as burnout, work-life balance, and organizational support were the main concerns in academic journals. The impact of the Covid 19 pandemic on employee mental health is discussed in the most appropriate article. Three main clusters emerged from the VOSviewer visualization: (1) burnout and mental health, (2) employees and evaluation, and (3) COVID-19 and the pandemic. As this study shows, cooperation between researchers and institutions has grown, but there are still opportunities for further research, especially on understudied topics such as burnout and meta-analysis. It is hoped that these findings will help policy makers and human resource practitioners create evidence-based strategies and policies to improve employees' mental well-being in the workplace.